Evolution of Innovative Surgical Techniques Using the Example of Selective Splenorenal Anastomosis Surgery - A. Yu. Anisimov; F. B. Mavlonov; D. E. Erkinova; A. I. Andreev; R. A. Ibragimov; E. Yu. Mandryka (Неотложная медицинская помощь)
RELEVANCE Despite the obvious successes of transjugular intrahepatic portosystemic shunt and orthotopic liver transplantation in some high-tech centers of the Russian Federation, the relevance of substantiating the use of selective splenorenal anastomoses in the treatment plan for portal hypertension, when hundreds of patients return to emergency surgery departments every year after conservative treatment with new episodes of bleeding, liver failure and high mortality rates, is beyond doubt.AIM OF THE STUDY To substantiate the viability of the selective splenorenal anastomosis operation by improving the technique of performing the intraoperative vascular maneuver exposure and venous reconstruction through the use of original modern innovative approaches.MATERIAL AND METHODS A retrospective controlled clinical study included 56 patients with intrahepatic portal hypertension with relatively preserved liver function, in whose complex treatment program for secondary prevention of bleeding, various options for selective splenorenal bypass surgery were used. In 21 patients of comparison group A, who were treated between 2006 and 2017, selective splenorenal anastomoses were performed using the traditional technique. In 35 patients of the main group B, who were treated between 2018 and 2021, the surgical technique was improved through the use of two innovative surgical techniques: intraoperative vascular maneuver exposure and venous reconstruction during the formation of a splenorenal shunt.RESULTS Original intraoperative vascular maneuver exposure at the first stage of surgery in patients with portal hypertension provides convenient volumetricspatial relationships in the surgical wound, creates comfortable conditions for performing the main surgical technique, vascular anastomosis. The duration of surgical interventions in patients of group A was 35% longer, and the average intraoperative blood loss was 58.6% higher than in patients of group B. The difference was statistically significant. The suggested intraoperative maneuver of vascular exposure has a minimal risk of developing specific complications associated with the approach to the vessels of the left retroperitoneal space.Seven days after the operation, patients in both groups showed a decrease in the size of the portal and splenic veins and the volume of the spleen. The blood flow velocity indices in the portal vein decreased, while those in the splenic vein increased. Turbulent blood flow was observed in the lumen of the shunts. No thrombosis of vascular conduits was detected in the early postoperative period according to Doppler ultrasound data. The observed differences were statistically insignificant.In group A, 7 patients (33.3%) died during the study period, and in group B, 3 patients (8.6%). The differences in mortality were statistically significant. The survival rate of patients in group A was significantly lower than that of patients in group B.CONCLUSION Changing the technique of execution through the use of modern innovative surgical techniques intraoperative vascular maneuver exposure and venous reconstruction during the formation of the splenorenal shunt allowed to improve the treatment results of patients with portal hypertension, reduce the duration of surgical interventions from 305.5±44.3 to 198.6±21.1 min (p=0.00155), average intraoperative blood loss from 930.0±198.6 to 385.1±84.7 ml (p=0.00004), reduce the incidence of complications in the early postoperative period, including postoperative pancreatitis from 19.0% to 0, anastomotic thrombosis from 28.6% to 5.7%, and mortality from 33.3% to 8.6% (p<0.05), increase the 8-week survival rate, thereby confirming the viability of the selective shunt operation splenorenal anastomosis, conditioned by the reserve for evolution built into it by the authors .When performed in a center with technical expertise, the procedure provides long-term survival and reliable hemostasis, potentially obviating the need for liver transplantation in a significant number of appropriately selected patients with portal hypertension and relatively preserved liver function.